The directionality of reduplicative plurality. (March 2022) - Berg, Thomas
Abstract : One instantiation of the well-known suffixing preference is the strong predominance of suffixes over prefixes in nominal-plural marking. Plurality may also be expressed by (partial) reduplication. In contradistinction to the rightward bias of affixes, reduplication in general exhibits a leftward bias. These opposite effects lead to a notable prediction regarding the directionality of reduplicative plurals, which are expected to show a compromise between the rightward bias of affixing and the leftward bias of reduplication. This prediction is not borne out in a sizeable sample of languages with reduplicative plurals. Almost all these languages put the reduplicant in word-initial position. That is, the leftward bias in reduplicative plurals is even more pronounced than that in reduplication generally. The explanation of this striking set of results revolves around a conspiracy of several factors which render the occurrence of word-final reduplicative plurals extremely unlikely. Thus, word-initial and word-final sites are much more unequal competitors in reduplicative plurality than prefixes and suffixes are in affixal plural marking.